Environmental themes in natural sciences textbooks: an analysis based on the macro-trends of environmental education - Eduardo Leite Vieira; Albaneide Fernandes Wanderley (Universidade Estadual de Alagoas, 2023)
Environmental Education is seen as one of the main ways to raise awareness in society and mitigate environmental degradation. The school space is one of the essential places to provide the citizen development of students, so that they can act with environmental responsibility. Thus, the present work aims to analyze the contents of Environmental Education in the PNLD 2021 books belonging to Moderna Plus collection - Nature Sciences, used in the New High School (NEM) in a public school in the city of Santa Helena, Paraíba. The new PNLD books are organized by knowledge area, and 06 didactic copies are offered for the three high school grades. The research was characterized as exploratory and documentary, with the analysis based on the contributions of the work of Layrargues and Lima (2014), related to the conservative, pragmatic and critical strands of the Political-Pedagogical Macrotrends of Environmental Education. The themes selected to be analyzed stemmed from the themes related to EE, addressed by each book that makes up the collection under investigation. This research presents all environmental proposals inserted in the Moderna Plus - Nature Sciences collection, through the macrotrends, as well as points out some factors that were not addressed in some of the didactic copies, which serve to assist teachers and students of the NEM, following the principles of the National Common Curricular Base (BNCC), through the implementation of the NEM.